The Effect of Low Temperature Stress on the Leaves and MicroRNA Expression of Potato Seedlings - Yan, Chongchong; Zhang, Nan; Wang, Qianqian; Fu, Yuying; Wang, Feng; Su, Yanbin; Xue, Bingjie; Zhou, Lin; Liao, Huajun (Frontiers in Ecology and Evolution, 2021)
In recent years, with the wanton destruction of the ecological environment by humans and the frequent occurrence of extremely bad weather, many places that should have been warm and blooming in spring, but the phenomenon of ‘April blizzard’ frequently appeared in the spring, which has seriously affected my country's crops, especially spring potato production in most areas. Potato cultivars, especially potato seedlings, are sensitive to frost, and low-temperature frost has become one of the most important abiotic stresses affecting potato production. Potato cold tolerance is regulated by a complex gene network. Although some low-temperature resistant microRNAs have been identified, little is known about the role of miRNAs in response to low-temperature stress in potatoes. Therefore, the objective of this study is to clarify the influence of low-temperature stress on the miRNA expression of potato by comparing the expression differences of miRNA in the potato which was treated with different low temperatures. 307 known miRNAs belonging to 73 small RNA families and 211 novel miRNAs were obtained, with the temperature decreased, the number of both known and novel miRNA decreased, and the minimum temperature was at -2 °C. Most of the miRNAs respond to low temperature, drought, and disease stress; some conserved miRNAs were first found to respond to low-temperature stress in potatoes, such as stu-miR530, stu-miR156d and stu-miR167b. The Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis of 442 different expression miRNAs target genes indicated that there existed diversified low-temperature responsive pathways, but Abscisic Acid was found likely to play a central coordinating role in response to low-temperature stress in many metabolism pathways. Quantitative Real-time PCR assays indicated that the related targets were negatively regulated by the tested different expression miRNAs during low-temperature stress. The results indicated that miRNAs may play an important coordination role in response to low-temperature stress in many metabolic pathways by regulating abscisic acid and gibberellin, which provided insight into the roles of miRNAs during low-temperature stress, and would be helpful for alleviating low-temperature stress and promoting the low-temperature resistant breeding in potatoes.